Development and Validation of a Questionnaire on Knowledge, Attitudes, and Practices Regarding the Use of Natural Medicine in Diabetes Mellitus: Development and Validation of a Questionnaire on Knowledge, Attitudes, and Practices Regarding the Use of Natural Medicine in Diabetes Mellitus - sasongko, santi setiani (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2025)
The use of natural ingredient drugs as complementary therapy for diabetes mellitus (DM) is increasing, both globally and in Indonesia. DM patients often seek alternatives or complements to conventional treatment with the hope of managing blood sugar levels, reducing medication side effects, or improving quality of life. Therefore, it is important to have a valid and reliable measurement tool to identify the level of knowledge, attitudes, and actions of patients regarding herbal medicine. This study aims to develop and validate a questionnaire that measures patients' knowledge, attitudes, and actions regarding the use of natural substance drugs in Diabetes Mellitus (DM). The development of the questionnaire was carried out through several stages: (1) Identification of concepts based on literature and previous research, (2) Development of questionnaire items, (3) Content validation by two experts (expert judgment), (4) Language comprehension test on five respondents, and (5) Validity and reliability test on 30 DM patients. The resulting questionnaire consists of three sections: knowledge (10 items), attitude (12 items), and actions (7 items). The results of the developed questionnaire proved to be valid and reliable for evaluating patients' understanding of herbal medicine in diabetes mellitus. Keywords: Natural ingredient medicine, diabetes mellitus, instrument validation.